Manajemen Kesan Melalui Penggunaan Avatar Roblox pada Ikatan Mahasiswa Muhammadiyah - Rendy Fathan Zulfa; Mustiawan Mustiawan; Andys Tiara (Dinasti Research, 2026)
Roblox functions not only as a source of entertainment but also as a space for communication and impression management in digital environments. Although research on avatars in digital environments has continued to develop, studies examining impression management through Roblox avatars among members of student organizations with specific values and norms remain limited. This study aims to analyze impression management through the use of Roblox avatars among members of the Muhammadiyah Student Association (Ikatan Mahasiswa Muhammadiyah). This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation involving five members of the Muhammadiyah Student Association (IMM) from South Jakarta who were selected through purposive sampling. The data were then analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that, first, the intensity of gameplay and the use of paid digital representations show that IMM members engage in relatively high-intensity gaming, which may potentially lead to negative impacts, including decreased academic performance and physical and psychological health problems. Second, this study finds differences in impression management between the real-world and virtual environments. In the real world, Islamic values and norms remain important considerations in the presentation of self. In contrast, impression management in the virtual environment is more expressive and flexible, resulting in a disparity between the identities presented through Roblox avatars and the informants' actual identities as IMM members. Future research is expected to expand the research objects and number of informants, employ a longer research period, and examine other factors that influence impression management in virtual environments.